2018
DOI: 10.1159/000488779
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Visceral Adiposity and Muscularity Predict Poor Outcomes after Hepatectomy for Hepatocellular Carcinoma

Abstract: Objective: Visceral adiposity, defined as a high visceral-to-subcutaneous adipose tissue area ratio (VSR), has been shown to be associated with poor outcomes in several cancers. However, in the surgical field, the significance of visceral adiposity remains controversial. The present study investigated the impact of visceral adiposity as well as sarcopenic factors (low muscularity) on outcomes in patients undergoing hepatectomy for hepatocellular carcinoma (HCC). Patients and Methods: This retrospective study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 59 publications
4
97
1
1
Order By: Relevance
“…Such findings reinforce the proposed mechanism related to the role of proinflammatory cytokines secreted by metabolically active adipocytes or adipose tissues in the development and progression of sarcopenic obesity [11]. Moreover, during the aging process, the shift of adipose tissue from subcutaneous to visceral adipose sites along with skeletal muscle atrophy leads to an imbalance between proinflammatory adipokines and anti-inflammatory myokines [14]. This unfavorable adipokine/cytokine profile represents a common mechanism for sarcopenia, obesity and immune senescence in elderly populations [15].…”
Section: Pathogenesis Of Visceral and Subcutaneous Fat And Its Relatisupporting
confidence: 85%
“…Such findings reinforce the proposed mechanism related to the role of proinflammatory cytokines secreted by metabolically active adipocytes or adipose tissues in the development and progression of sarcopenic obesity [11]. Moreover, during the aging process, the shift of adipose tissue from subcutaneous to visceral adipose sites along with skeletal muscle atrophy leads to an imbalance between proinflammatory adipokines and anti-inflammatory myokines [14]. This unfavorable adipokine/cytokine profile represents a common mechanism for sarcopenia, obesity and immune senescence in elderly populations [15].…”
Section: Pathogenesis Of Visceral and Subcutaneous Fat And Its Relatisupporting
confidence: 85%
“…Although these results were discrepant with other findings 15,26 , our data were consistent with a recent report showing that age and obesity were found to be independently associated with sarcopenia in patients undergoing liver transplant evaluation 27 . Previous studies have reported that patients with sarcopenic obesity had worse survival in hepatocellular carcinoma receiving hepatectomy or after living donor liver transplantation [28][29][30][31] . While our data in accordance with a recent study showed that sarcopenicobesity was not a prognostic factor in patientsundergoingliver resection for CRLM 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratio (OR) reported for post hepatectomy liver failure (PHLF) prediction by sarcopenia was 2.44 (95% CI 1.20–4.99, p = 0.012). More recent studies [ 24 , 25 ] showed the role of sarcopenic obesity on prognosis after hepatectomy; in the study by Kobayashi et al [ 25 ] patients were classified on the basis of body composition into four groups as non-sarcopenic non-obesity (39%), non-sarcopenic obesity (47%), sarcopenic non- obesity (7%) and sarcopenic obesity (7%). The OS and the recurrence-free survival rates after hepatectomy for HCC were significantly lower in the sarcopenic obesity group than in the non-sarcopenic non-obese group ( p = 0.002 and p = 0.003, respectively).…”
Section: Curative Treatmentsmentioning
confidence: 99%